Merebut Sekolah Turki: Represi Transnasional Rezim Islamis dan Pembersihan Sekolah Gülen di Indonesia - Yusli Effendi (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2019)
This paper seeks to address Erdoğan’s transnational repression towards Turkish citizens and Gülen-linked schools in Indonesia which are denounced as part of Fethullahçı Terör Örgütü/Fethullah Gülen Terror Organization (FETÖ)’s most vital source of funding. It is argued that the AKP-ruled government effectively transferred political hostilities from authoritarian Turkey to democratic Indonesia in micro-level targeting Turkish Gülenist teachers and other Hizmet Movement adherents. In exercising extraterritorial coercive acts, the regime relied on institutional outposts such as the embassy, consulate, and mission. These proxy regime institutions played an agressive role in the repression of the Turkish diaspora, including active surveillance, nationality deprivation, and intimidation of the dissent’s family members. They also have tried to shut down, take control, or take over nine Indonesia’s Gülen-linked educational institutions to The Maarif Foundation (TMF). Nevertheless, in this meso-level (the Gülen Movement as a transnational network), The Turkish Government have failed to purge Gülen-linked schools whose their cooperation with PASIAD—which is associated with FETO—was terminated in 2015. Employing qualitative approach and data combined with content analysis, this study contributes in explaining Erdoğan regime’s coercive power across border which meets its middle power counterpart. One of the more significant findings to emerge from this study is that extraterritorial repressive acts were hindered by the national law and sovereignty of political opponents’ host country. Keywords: transnational repression, authoritarianism beyond state, Gülen Movement, Indonesia’s Turkish schools